Development, validation of QuEChERS-based method for simultaneous determination of multiclass pesticide residue in milk, and evaluation of the matrix effect. Issue 5 (4th May 2019) - Tripathy, Vandana; Sharma, Krishan Kumar; Yadav, Rajbir; Devi, Suneeta; Tayade, Amol; Sharma, Khushbu; Pandey, Priya; Singh, Gitansh; Patel, Amar Nath; Gautam, Rahul; Gupta, Ruchi; Kalra, Shobhita; et al.
Abstract: Extraction and quantification of pesticide residue from the milk matrix at or below the established maximum residue limit (MRL) is a challenging task for both analytical chemists and the regulatory institutions to take corrective actions for the human health and safety. The main aim of the study is to develop a simple rapid and less expensive QuEChERS extraction and cleanup method for simultaneous analysis of 41 multiclass pesticide residue in milk by gas chromatography-electron capture detector (GC-ECD), followed by confirmation of the residues with gas chromatography-mass spectrometer (GC-MS). Effect of sorbent type, temperature, spiking concentration, matrix effect (ME), measurement uncertainty (MU), inter- and intra-assay repeatability, reproducibility of recovery, and trueness of the results were investigated to validate the effectiveness of the method. Limit of determination (LOD) and limit of quantitation (LOQ) for all the analytes ranged within 0.001–0.02 and 0.002–0.05 µg mL −1, respectively. The % recovery of all the pesticides ranged between 91.38 and 117.56% with relative standard deviation (RSD) below 2.79%. The MU for all the analytes was ≤29% of respective LOQs, and except for few pesticides, the ME was largely negative. The method fulfilled all the SANTE guidelines and thus can be extended for routine analysis of multiclass pesticide residue in milk.